Development of Flashcard Media On Indonesia for Studen At Grade 2 Elementary School - Nova Adelia Febriani; Ratih Asmarani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Learning media is a very essential object in the teaching and learning process. This research develops a flashcard EBI teaching aid product by containing Indonesian Spelling material. The purpose of this research is to develop a valid, attractive, and effective flashcard EBI teaching aid product during teaching and learning activities at SDN Ceweng. This study involved 17 students of SDN Ceweng in the even semester of the 2021/2022 academic year. This development research uses the ADDIE development model. the results of this study indicate that: (1) the results of the validity of the media obtained a percentage value of 86.76% with a very valid category and suitable for use without improvement; (2) the results of the validity of the material obtained a percentage value of 82.35% with a very valid category and suitable for use without improvement; (3) interesting implementation results, namely 89.82% with very interesting category. Based on the acquisition value, the flashcard EBI flashcard media is declared suitable for use in the learning process. Keywords: Flashcard, Indonesian Spelling